A case report and focused literature review of d‐penicillamine and severe neutropenia: A serious toxicity from a seldom‐used drug. Issue 5 (9th April 2019) - Pitman, Stuart K.; Huynh, Tony; Bjarnason, Thorarinn A.; An, Josiah; Malkhasyan, Karen A.
Key Clinical Message: Prescribingd ‐penicillamine for Wilson's disease must be accompanied by vigilant monitoring, including a complete blood cell count with differential. For most, this should occur once or twice weekly during the first month of therapy and during periods of dose escalation, then every two weeks for six additional months, then monthly. Abstract : Prescribingd ‐penicillamine for Wilson's disease must be accompanied by vigilant monitoring, including a complete blood cell count with differential. For most, this should occur once or twice weekly during the first month of therapy and during periods of dose escalation, then every two weeks for six additional months, then monthly.